Ignition, Combustion, and Mechanical Properties of Briquettes from Coal Slime and Oil Waste, Biomass, Peat and Starch - Vershinina K. Yu. Kseniya Yurievna; Dorokhov V. V. Vadim Valerjevich; Romanov D. S. Daniil Sergeevich; Strizhak P. A. Pavel Alexandrovich (2023, 2023)
Title screen